(untitled) (The Research of Medical Science Review, 2025)
Hamal Lake, an integral wetland in Pakistan's Sindh province, plays a vital role in supporting avian biodiversity, particularly as a stopover site for migratory birds along the Indus Flyway. This study examines the seasonal abundance and diversity of migratory bird species at Hamal Lake to understand patterns and ecological significance. Field surveys were conducted across all four seasons, employing direct observation, point count methods, and species identification through standard field guides. Results revealed notable seasonal fluctuations in bird populations, with peak diversity observed during winter months, coinciding with the arrival of waterfowl and shorebirds from Central Asia. Habitat quality, water levels, and food availability emerged as key factors influencing bird presence and species richness. This research underscores the importance of preserving Hamal Lake's ecological integrity to sustain migratory bird populations and highlights its role in regional biodiversity conservation. Further studies are recommended to monitor long-term trends and address anthropogenic threats to this critical habitat.